Isaiah's legacy : [large type] / a novel of prophets & kings - Andrews, Mesu, 1963- (Andrews, Mesu, 1963- Novel of prophets & kings, 2020)
"At eight years old, Shulle has known only life in a small village with her loving but peculiar father. When Uncle Shebna offers shelter in Jerusalem in exchange for Shulle's help tutoring King Manasseh, Judah's five-year-old co-regent who displays the same peculiarities as her father, she's eager to experience the royal court. But Shulle soon realizes the limits of her father's strict adherence to Yahweh's Law when Uncle Shebna teaches her of the starry hosts and their power"--Provided by publisher.